Técnicas de comunicación para mejorar el rendimiento académico en los estudiantes del décimo “A” colegio 27 de Febrero, sección vespertina, ciudad de Loja 2016-2017 - Medina Angamarca, Marco Antonio (2018)
The present research entitled Communication Techniques to improve Academic Performance in students of the Tenth "A” at February 27 school, afternoon section, city Loja 2016-2017; its objective was to implement communication techniques to improve the academic performance of students. Descriptive, cross-sectional study and pre-experimental design; the methods were used: scientific, deductive, inductive, statistical, analytical and synthetic. In order to diagnose the type of academic performance of the students, the grades of the second and third partial (to be considered in the before and after), likewise to determine the type of performance, the grades were classified according to the rating scale of the Ministry of Education of Ecuador; in such a way, the results are: 34.79% of researched do not reach the Required Learning (NAAR scores between equal or less than 4) in the Mathematics subject; 43.48% have Next Scores to Achieve Required Learning (PAAR scores between 4.01 to 6.99) in Social Studies 39.13%. In both Science and Language and Literature are in the same type; after the application of the intervention proposal (workshop) on communication techniques, worked with the 8 teachers (sample), the students improved the academic performance reaching percentages as: (AAR scores between 7.00 to 8.99) Reached the required learning , in Mathematics (47.82%); Social Studies (52.18%), in Science (56.52%); the type (DAR scores between 9.00 to 10) Dominate the Required Learning in Language and Literature (43.48%) of the students. Concluding that students managed to master and achieve required learning, validating the effectiveness of communication techniques and promoting the development of good communication between teachers and students in the teaching and learning process.